Forewarned is forearmed: rice plants develop tolerance to post-anoxia during anoxic conditions by proteomic changes - Shikov, Anton E.; Shost, Valeriya I.; Chirkova, Tamara V.; Shishova, Maria F.; Yemelyanov, Vladislav V. (Frontiers in Plant Science, 2025)
IntroductionIn the absence of oxygen (anoxia), plants suffer from an energy shortage. Subsequent return to normoxia could exacerbate the obtained damage through severe oxidative stress. Thus, in nature, post-anoxia is a broad combination of stressors. The efficient recovery after oxygen depletion can occur only by the activation of defensive systems.MethodsIn this study, we analyzed the impact of anoxia and re-aeration on tolerant rice at a proteomic level using two-dimensional gel electrophoresis followed by mass spectrometry. We further used bioinformatic predictions to reveal transcription factors modulating stress-induced gene expression.ResultsMass spectrometry revealed 82 spots corresponding to 13 and 8 unique proteins in shoots and roots, respectively. Spot-wise clustering illustrated that the re-aeration-related proteome resembles ones in the anoxic but not the control conditions. We classified proteins into four groups according to the intensities of spots under distinct conditions and observed that anoxia- and reoxygenation-specific proteins constituted a minor fraction (24%), unlike the other two. One of them contained proteins whose content continually decreased during stress, such as RuBisCO and fructose-bisphosphate aldolase. The second group included proteins whose synthesis started in anoxia and reached a peak during re-aeration. It involved OEE1 (oxygen-evolving enhancer protein 1), heat shock proteins, and pathogenesis-related (PR) proteins, implying defense from oxidative damage and pathogens to which plants become vulnerable during re-aeration. Promoter regions of genes encoding these proteins were enriched with transcription factor binding sites of stress-related TFs, both well-studied (ERF, WRKY, MYB) and not as frequently discussed in such contexts (TCP, TBP, SBP).DiscussionBy comparing our observations with proteomic and transcriptomic research, we revealed that plant reactions to anoxia and reoxygenation are starkly similar. Extrapolating out results based on pure anoxia and reoxygenation, we suggest that rice shoots and roots become pre-adapted to the post-anoxic period in broad terms during oxygen depletion.